The Word according to Eve : women and the Bible in ancient times and our own - Murphy, Cullen (New York : Houghton Mifflin, 1999)
"In the world that created the Bible, there were no female scholars and theologians; yet since World War II, owing to such stunning discoveries as the Dead Sea Scrolls and the Nag Hammadi texts and to advances in historical understanding, a new generation of scholars has found new ways of reading the Scriptures - including querying the role that male divines have traditionally assigned to women, both those who populate the Bible and those living in the modern world." "Surveying the new scholarship and the personalities of those who have created it, The Word According to Eve not only explores afresh the history of our religions but offers exciting new challenges to our sense of worship."--Jacket
" A Peter Davison Book."
Includes bibliographical references and index
Keywords: Bible and Feminism